Innovation for Development and the Role of Government : A Perspective from the East Asia and Pacific Region - Fan, Qimiao; Li, Kouqing; Zeng, Douglas Zhihua; Dong, Yang; Peng, Runzhong (Washington, DC : World Bank, 2012)
This book is the result of a joint forum on 'innovation for development' held by the World Bank and the China-based Asia-Pacific Finance and Development Center (AFDC) in Shanghai in September 2006. The book examines the relationship between innovation, competitiveness, and economic growth; the role of innovation in financial sector development; and specific government policies for innovation in China. Development is one of the major themes of today's world. In the context of global economic development practices, the development patterns of various countries fall primarily into three categories. The first is the resources-based pattern, which is supported by natural resource endowments. The second category is the dependency pattern, which is determined by a country's adjacency to economically developed countries with which it has close economic ties. The third is the innovation-based pattern, which is driven by innovation. Measured by levels of economic development, the current top 20 most developed countries in the world have opted primarily for an innovation-driven pattern. In addition, from three perspectives, namely, the creation of an innovation regime, innovation-oriented fiscal and financial policies, and regional cooperation on innovation, and in two dimensions, namely, theory and practice, the book discusses and explores problems facing us all now and challenges in the future. The viewpoints in this book both reflect the research on the issues of innovation by its authors and, to a certain extent, mirror the views expressed by nonspeaker experts in the course of discussions at the 2006 forum. Economic globalization is an inevitable trend. It is extremely necessary and valuable to conduct research on, and exchange views about, innovation and development against the backdrop of constantly deepening economic globalization. First and foremost, this helps us to see through the vast and complex economic surface to examine and discover the laws that drive sustainable economic development. Second, through sharing experiences of innovation among different countries, it can help us to establish a cooperative mechanism for innovation that can transcend social systems and cultural differences and promote the harmonious economic development for the region.